PM Motors for High Efficiency Applications - Martins, Carlos Eduardo G.; Nau, Sebastião Lauro (Neutro à Terra, 2016)
PM motors are suitable for nearly all applications, like pumps, elevators, compressors, blowers, extruders, generators, electric vehicles, servodrives, cooling towers, household appliances, etc. This paper will present some applications where the use of PM motors allowed for enhancements in energy efficiency and process quality.